Patients' Experiences With Staphylococcus aureus and Gram-Negative Bacterial Bloodstream Infections: Results From Cognitive Interviews to Inform Assessment of Health-Related Quality of Life. (8th December 2021) - King, Heather A; Doernberg, Sarah B; Grover, Kiran; Miller, Julie; Oakes, Megan; Wang, Tsai-Wei; McFatrich, Molly; Ruffin, Felicia; Staman, Karen; Lane, Hannah G; Rader, Abigail; Sund, Zoë; et al.
Abstract: Background: We previously conducted a concept elicitation study on the impact of S taphylococcus aureus and gram-negative bacterial bloodstream infections (SAB/GNB) on health-related quality of life (HRQoL) from the patient's perspective and found significant impacts on HRQoL, particularly in the physical and functional domains. Using this information and following guidance on the development of patient-reported outcome (PRO) measures, we determined which combination of measures and items (ie, specific questions) would be most appropriate in a survey assessing HRQoL in bloodstream infections. Methods: We selected a variety of measures/items from the Patient-Reported Outcomes Measurement Information System (PROMIS) representing different domains. We purposefully sampled patients ~6–12 weeks post-SAB/GNB and conducted 2 rounds of cognitive interviews to refine the survey by exploring patients' understanding of items and answer selection as well as relevance for capturing HRQoL. Results: We interviewed 17 SAB/GNB patients. Based on the first round of cognitive interviews (n = 10), we revised the survey. After round 2 of cognitive interviewing (n = 7), we finalized the survey to include 10 different PROMIS short forms/measures of the most salient HRQoL domains and 2 adapted questions (41 items total) that were found to adequately capture HRQoL. Conclusions: We developed a survey from well-established PRO measures that captures what matters most to SAB/GNB patients as they recover. This survey, uniquely tailored to bloodstream infections, can be used to assess these meaningful, important HRQoL outcomes in clinical trials and in patient care. Engaging patients is crucial to developing treatments for bloodstream infections.